1992
DOI: 10.1093/jnci/84.22.1740
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Folate Deficiency and Supplementation on Methylnitrosourea-Induced Rat Mammary Tumors

Abstract: Since the rat is relatively resistant to folate deficiency anemia, other animal models should be used to test the effect of folate nutriture on carcinogenesis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

6
38
0
3

Year Published

1995
1995
2011
2011

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 78 publications
(47 citation statements)
references
References 0 publications
6
38
0
3
Order By: Relevance
“…One potential harmful consequence of folate fortification is the risk of modification on DNA methylation (10). In some animal studies, dietary folate deficiency can inhibit rather than enhance the development of breast cancer in rats (43,44), which is in contrast to the observation in epidemiologic studies. It suggested that folate possesses dual effects on carcinogenesis depending on the time and dose of folate intake.…”
Section: Discussionmentioning
confidence: 91%
“…One potential harmful consequence of folate fortification is the risk of modification on DNA methylation (10). In some animal studies, dietary folate deficiency can inhibit rather than enhance the development of breast cancer in rats (43,44), which is in contrast to the observation in epidemiologic studies. It suggested that folate possesses dual effects on carcinogenesis depending on the time and dose of folate intake.…”
Section: Discussionmentioning
confidence: 91%
“…Furthermore, promotion of in-stent restenosis after high dose folic acid has been observed (Lange et al, 2004). It was recently suggested that high dose folic acid might promote DNA hypomethylation and tumor growth (Baggott et al, 1992;Bills et al, 1992). These results highlight the necessity of determining the maximum tolerable dose of folic acid, taking into consideration effects on liver function.…”
Section: Discussionmentioning
confidence: 97%
“…Previous animal studies conducted in another chemical carcinogen rat model collectively suggest that mild dietary folate deficiency inhibits, whereas folic acid supplementation (4-20Â BDR) does not modulate, the development and progression of mammary tumors (25,26,38). In these studies, dietary folic acid supplementation was initiated only at weaning (25,26,38), suggesting that in utero supplementation has a drastically different effect on mammary tumor risk.…”
Section: Discussionmentioning
confidence: 98%
“…In these studies, dietary folic acid supplementation was initiated only at weaning (25,26,38), suggesting that in utero supplementation has a drastically different effect on mammary tumor risk. In contrast to the present study, we have previously reported that maternal folic acid supplementation provided in utero and during lactation significantly reduced the number of terminal end buds of the mammary glands at puberty, a purported biomarker of mammary tumor risk in rodents (23,24), in the offspring (39).…”
Section: Discussionmentioning
confidence: 99%